(untitled) (Research, Society and Development, 2022)
The hegemony of knowledge in administration from a sociological functionalist paradigm has resulted in a long-term scenario of asymmetry and injustice in the administration/management field. Nevertheless, the decolonial perspective has gained ground with recent works that use the approach to expand research agendas in administration. This work asked the possibilities of using decolonial perspectives in administration/management present in the area literature and, for this, a systematic literature review was made out. The results reveal that researchers have been successful in debating several themes under the light of a decolonial perspective. We bring as a theoretical contribution the understanding that the reinforcement of the North-South dichotomy or the radical essentialist position is not the path pointed out by the articles and we defend that being “northless” is important, in the sense of delinking the North as the main reference point, but without ignoring it.